A collaborative small-group discussion approach to improving fifth graders' use of academic, relational, social, and emotional vocabulary. (2021) - Hsieh, Ming-Yi; Lin, Tzu-Jung; Sallade, Rebecca; Ha, Seung Yon; Kraatz, Elizabeth; Shin, Sangin
Highlights: Small-group discussion promoted pupils' academic and social-emotional learning. Collaborative social reasoning approach fostered pupils' vocabulary learning. Collaborative discussion on social-moral texts facilitated vocabulary use in essays. Reflective essays demonstrated pupils' academic and social-emotional vocabulary use. Abstract: This study examined the impacts of a collaborative small-group discussion intervention on fifth graders' use of vocabulary as they reasoned about literature involving complex social-moral issues. A total of 250 fifth graders (120 males and 130 females) from 12 classrooms in two public middle schools in the Midwestern United States participated in this six-week quasi-experimental study. Classrooms were assigned to one of three conditions: Collaborative Social Reasoning (CSR: intervention), Read Aloud (RA), or Regular Instruction (RI). Use of vocabulary was measured through a reflective essay task before and after the intervention. Results showed that students in the CSR condition generated more academic and relational vocabulary than students in RA and RI conditions. The CSR students outperformed the RI students in the use of social and emotional vocabulary. Findings shed light on possible mechanisms of small-group discussion in promoting fifth graders' academic and social-emotional learning.